A Survey On Telugu Optical Character Recognition From Digital Images - et. al., Srinivasa Rao Dhanikonda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Images play an essential function in the electronic media to share information. Nowadays, each event is going to be recorded in the arrangement of digital images. Text from the image file won't be in a format on the computer. OCR (Optical Character Recognition) for English vocabulary is well constructed. Currently, there's a requirement of OCR for Indian languages to maintain historical documents composed mainly in Indian languages to arrange publications in the library and for program form processing. OCR for the Telugu language is challenging as consonants and vowels plays a vital role in forming words along with vattus and gunithas. It may be a mixture of vowels and consonants that may form a compound character. This paper presents research on methods utilized in the OCR method for the Telugu Language until today.